2002
DOI: 10.1029/2000je001439
|View full text |Cite
|
Sign up to set email alerts
|

Combined remote mineralogical and elemental identification from rovers: Field and laboratory tests using reflectance and laser‐induced breakdown spectroscopy

Abstract: [1] Rover mast-based stereo imaging, reflectance or emission spectra, and laser-induced breakdown spectroscopy (LIBS) provide powerful synergistic data sets for rapidly determining geologic setting, mineralogy, and elemental composition for rock and soil targets. We report results from hand specimen examination, multiple spectral reflectance (VISIR, 0.4-2.5 mm), and remote LIBS measurements for representative samples (basalt, iron oxides, altered rhyolite, and dolostone) collected during the May 2000 rover tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 16 publications
0
43
0
2
Order By: Relevance
“…The combination of Raman and LIBS techniques yields complementary information about the sample under examination [87]. Wiens et al [71] reported the advantages of combining both techniques in a single instrument for stand-off analysis at distances up to 8 m. In this work, the authors demonstrated the feasibility of and synergy of the Raman/LIBS instrument for the chemical identification of minerals at distances. One of the major fields of application of this combination is the chemical analysis of rock, soils and materials of geological interest for planetary explorations and space missions.…”
Section: New Trends In Stand-off Libsmentioning
confidence: 69%
See 1 more Smart Citation
“…The combination of Raman and LIBS techniques yields complementary information about the sample under examination [87]. Wiens et al [71] reported the advantages of combining both techniques in a single instrument for stand-off analysis at distances up to 8 m. In this work, the authors demonstrated the feasibility of and synergy of the Raman/LIBS instrument for the chemical identification of minerals at distances. One of the major fields of application of this combination is the chemical analysis of rock, soils and materials of geological interest for planetary explorations and space missions.…”
Section: New Trends In Stand-off Libsmentioning
confidence: 69%
“…An initial field test of a stand-off LIBS instrument for applications in space missions was accomplished by Wiens et al [71]. This group started to develop LIBS for future use from a rover or lander on a planetary surface to remotely obtain elemental information on rocks and soils within 20 m of the instrument.…”
Section: Use Of St-libs For Planetary Explorationmentioning
confidence: 99%
“…The two methods are essentially complementary, however, while not all materials are Raman active, LIBS can in theory measure the composition of any target since all matter is composed of elements. The advantages of LIBS for in situ analysis has been recognized by several groups and it has found application in the field for environmental soil monitoring (Wainner et al, 2001;Harmon et al, 2005;Yamamoto et al, 1996;Mosier-Boss et al, 2002), survey of nuclear power plants (Whitehouse et al, 2001;Saeki et al, 2014) and recently planetary exploration (Wiens et al, 2002Maurice et al, 2012;Meslin et al, 2013).…”
Section: Underwater Libs At High Pressurementioning
confidence: 99%
“…This system was similar to that used in a previous study [2]. The second set-up was a prototype LIBS instrument used on 2000/2001 rover [3] and field tests. It consists of a compact flashlamp-pumped Nd:YAG laser (80 mJ/pulse, 0.1 Hz, 1064 nm), an adjustable beam focusing system (6.4 cm diameter lens) to focus the pulses on remotely located samples and collect the plasma light.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Very preliminary work on such remote LIBS measurements based on large laboratory type equipment was carried out about a decade ago [1]. Recent work has characterized the capabilities using more compact instrumentation [2] and some measurements have been conducted with LIBS on a NASA rover testbed [3].…”
Section: Introductionmentioning
confidence: 99%